2009
DOI: 10.1002/cvde.200906790
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Electrical Characterization of ZnO and Al‐doped ZnO Thin Films Deposited by MOCVD

Abstract: A novel approach is used to deposit transparent Al-doped zinc oxide (AZO) films by metal-organic (MO) CVD using a Zn/Al safe, friendly to use, easily to handle, multimetal, liquid precursor source. Films are highly crystalline, (002) textured, and exhibit good transparency in the visible region (90%). The effects of Al doping on morphological, optical, and electrical performances are scrutinized. Al doping causes an energy gap (Eg) blue shift and a slight decrease in refractive index. Moreover, it favors sizea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 36 publications
3
21
0
2
Order By: Relevance
“…[37,[42][43][44]. Tang et al [45] and Fragal et al [46] reported the relationship between optical band gap and Al doping concentration of the ZnO thin films. They observed that in un-doped ZnO films, the optical band gap appeared at 3.25 eV while it increased to 3.47 eV with Al doping.…”
Section: Optical Propertiesmentioning
confidence: 97%
“…[37,[42][43][44]. Tang et al [45] and Fragal et al [46] reported the relationship between optical band gap and Al doping concentration of the ZnO thin films. They observed that in un-doped ZnO films, the optical band gap appeared at 3.25 eV while it increased to 3.47 eV with Al doping.…”
Section: Optical Propertiesmentioning
confidence: 97%
“…Al‐doped ZnO thin films can be prepared by different technologies such as sol‐gel, spray pyrolysis, pulsed laser deposition (PLD), magnetron sputtering, and metalorganic chemical vapor deposition (MOCVD) 6–10. Among these techniques, magnetron sputtering is the most commonly used method because it is a low‐cost, simple, and safe method and it can produce high deposition rates at low temperature and obtain highly uniform and larger scale films with high packing density and strong adhesion 11.…”
Section: Introductionmentioning
confidence: 99%
“…13 Ar (250 sccm) and O 2 (250 sccm) were used as carrier and reaction gases, respectively and the total pressure in the reactor was about 5 Torr. Depositions were carried out for 1 hour min and the deposition temperature is 600 C. After that, polystyrene (PS, Aldrich) microbeads of 1 micron of diameter were deposited onto the seed layers by drop casting and allowed to self-assemble in ordered close-packed colloidal monolayers.…”
Section: Methodsmentioning
confidence: 99%